2019
DOI: 10.15171/jcvtr.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-L-methionine modulates radiation injury and Duox1 and Duox2 upregulation in rat’s heart tissues

Abstract: Introduction: Redox interactions play a key role in radiation injury including heart diseases. In present study, we aimed to detect the possible protective role of selenium-L-methionine on infiltration of immune cells and Duox1&2 upregulation in rat’s heart tissues. Methods: In this study, 20 rats were divided into 4 groups (5 rats in each) namely: irradiation; irradiation plus Selenium-L-methionine; control; and Selenium-L-methionine treatment. Irradiation (15 Gy to chest) was performed using a cobalt-60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Cardiovascular injury has been associated with radiation in cancer therapy (Eldabaje et al 2015 ), in which the redox modulation plays an important role. Therefore, selenomethionine (4 mg kg −1 ) was able to protect the rat heart tissue against radiation-induced injury by down-regulating the expression of dual oxidase (Duox1 and Duox2); two important pro-oxidant enzymes (Kolivand et al 2019 ).…”
Section: Pharmacology Of Organoselenium Compoundsmentioning
confidence: 99%
“…Cardiovascular injury has been associated with radiation in cancer therapy (Eldabaje et al 2015 ), in which the redox modulation plays an important role. Therefore, selenomethionine (4 mg kg −1 ) was able to protect the rat heart tissue against radiation-induced injury by down-regulating the expression of dual oxidase (Duox1 and Duox2); two important pro-oxidant enzymes (Kolivand et al 2019 ).…”
Section: Pharmacology Of Organoselenium Compoundsmentioning
confidence: 99%
“…However, despite substantially reducing the dose of the accidental irradiation, radiation-induced cardiac events continue to occur. Furthermore, research is exploring protective agents which interfere with one or more of the identified pathophysiological mechanisms of radiation-induced CVD mainly through reducing chronic inflammation and oxidative stress [ 44 , 210 , 211 ]. In addition, non-traditional therapies against CVD are worth exploring…”
Section: Discussionmentioning
confidence: 99%
“…Myocarditis refers to as localized or diffuse inflammatory lesions of the myocardium, initiated by infectious factors, most commonly, viruses and non‐infectious factors, such as systemic autoimmune disease, medications and cardiotoxins 40 . It is believed that IL‐13 consecutively contributes to regulating recruitment and differentiation of immune cells, chemokines secretion and fibrosis during the progression of myocarditis 40‐42 . IL‐13 deficiency mice develop into severe myocarditis in both coxsackievirus B3 (CVB3)‐induced model and experimental autoimmune myocarditis (EAM) model, manifested in decreased systolic and diastolic left ventricular functions and decreased survival 41 .…”
Section: Role Of Il‐13 In Cvdsmentioning
confidence: 99%